Research and Verification of Key Techniques in the Simulation of Space Extremely Rapid Decompression in Millisecond - Junwei Wang; Lei Zhang; Guohua Li; Ran Liu; Juan Ning; Xiao Han; Xin He (International Journal of Aerospace Engineering)
The research of rapid decompression with its effect assessment and protection technology is the problem that must be faced by the future exploration projects such as near space exploration, deep space exploration, and long-term lunar or Mars base. A new reusable quick opening mechanism which can be opened in millisecond is designed to meet the testing requirement of ground simulator for extremely rapid decompression, and the testing results show that the quick opening mechanism can be opened within 0.1 s. The mathematical formulation is also developed, and the comparisons with the results from the literature demonstrate its validity. The CFD simulation and the verification system are established for the airflow in the rapid decompression process under different opening degrees. The simulation results show that the effect of the opening on the decompression process is very obvious and the decompression time corresponding to 50%, 75%, and 100% opening is 479.1 ms, 320.7 ms, and 290.1 ms, respectively. The testing results also show a consistent trend which is 583 ms, 450 ms, and 384 ms, respectively, to reach the equilibrium state.